Approximation of Poisson Integrals by de la Vallée Poussin Sums - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
On the classes of Poisson integrals of functions belonging to unit balls in the spaces C and L, we obtain asymptotic equalities for the upper bounds of approximations by de la Vallée Poussin sums in the uniform metric and the integral metric, respectively.